The Hill of Six Lakes revisited: New data and re-evaluation of a key Pleistocene Amazon site - D'Apolito, Carlos; Absy, Maria Lúcia; Latrubesse, Edgardo Manuel (Quaternary Science Reviews, 2013)
The new analyses of a sedimentary record of Lake Pata in the Hill of Six Lakes, in NW Amazon and its correlation with other Quaternary proxy records in the region provide new insights regarding the vegetation and climate of the lowland forest during the Last Glacial. Despite what has been reported previously in the literature, the sedimentary and pollen records are not continuous. The hill remained forested; however, clear signals of structural change are seen in the record, which indicate that the area experienced a significantly drier climate during the Last Glacial Maximum (LGM). The herbs and taxa that are known to be more dominant in seasonally dry forests were all more abundant during the glacial part of the record, and the cool-adapted elements were mixed with warm lowland elements, which indicates a temperature depression. A comparison of the palaeoecological data with other regional geoenvironmental records of the Upper Negro River basin and other areas of the Amazon provides additional support for a cooler and more seasonal environment during the middle Pleniglacial, which then became drier during the LGM. A "wet" LGM is strongly refuted; therefore, the palaeoclimatic and ecological models that used the previous proxy data from Six Lakes to sustain "wet" conditions and a "continuous forest record" during the LGM to reconstruct the palaeoenvironmental conditions in the Amazon should be reviewed. © 2013 Elsevier Ltd.
Keywords: Amazonia; Ecological Models; Ice Age; Last Glacial Maximum; Palaeoecology; Pollen; Sedimentary Records; Temperature Depression; Climate Change; Ecology; Forestry; Glacial Geology; Sedimentology; Lakes; Data Set; Depositional Environment; Ecological Modeling; Herb; Lacustrine Deposit; Last Glacial; Last Glacial Maximum; Lowland Environment; Paleoclimate; Paleoecology; Pleistocene; Pollen; Proxy Climate Record; Ecology; Forestry; Lakes; Pollen; Amazonas; Amazonia; Lake Pata